matières, en continuité - Bruno Marchand (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère, 2021)
The purpose of this paper is to think about the issues underlying the animation of an urban studies journal. Based on the experience of the journal Environnement urbain/Urban Environment (EUE) – an independent, peer-reviewed and open access journal with a scientific committee – we show that the creation and maintenance of a journal in urban studies expresses a desire to structure the field and provide a framework for innovation, both in terms of practices and theories. By defining a specific intellectual project, the journal also allows for the existence and animation of a community of researchers, which is important when one considers that urban studies is a weakly institutionalized field with unclear boundaries. However, this added value tends to come up against the challenges of independent open access publishing, its meaning and, more generally, the role of a journal in research today.